Quality of dissertations of Isfahan Faculty of Dentistry during 2005‒2009 - Abasali Khademi; Aminolah Tavangar; Kobra Hosseinpour (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Doctoral dissertations are considered one of the most important sources of information and research activities. This study investigated the quality of doctoral dissertations of Isfahan Faculty of Dentistry during 2005‒2009.Materials and Methods: In this cross-sectional analytical study one hundred undergraduate and postgraduate dissertations dental students in Faculty of Dentistry were selected by simple random sampling procedure during 2005‒2009. A questionnaire was prepared for data collection, which was filled in qualitatively. The variables evaluated consisted of means of achieving the aims of the study, evaluation of hypotheses, sufficiency of study population size, correct statistical tests, materials and methods, arrangement of the references, preparation of the "discussion' and "conclusion", separately for each educational level. Chi-squared test was used for statistical analysis of data with SPSS software. Results: A total of 52% and 48% of the dissertations were observational and interventional, respectively, with 44% being descriptive. The results showed tha the highest overall evaluation scores belonged to animal studies (100 ± 0.00), the lowest belonged to case-control (84.63 ± 13.61) and descriptive studies 86.7 ± 7.56, respectively. Average MSc (19) and doctoral (81) dissertation evaluation scores were 90.84 ± 8.248 and 88.28 ± 8.872, respectively. A total of 78% and 80% of dissertations achieved their goals and hypotheses, respectively. A total of 97%, 78% and 98% had sufficient population sizes, used appropriate statistical methods and had well written discussions, respectively.Conclusions: Results showed that the strengths of these dissertations included well written discussions, literature reviews and reference lists. Errors were observed in preparation of hypotheses, aims, statistical analyses, and sample sizes. It appears it is necessary to improve the quality of dissertations by holding classes on research techniques and good writing for students since the dissertations will be finally shared with other researchers in the form of articles. Key words: Doctoral dissertation, Evaluation studies, Quality control.